Impact of COVID-19 on surgical emergencies: nationwide analysis. Issue 3 (22nd May 2021) - Lazzati, A; Raphael Rousseau, M; Bartier, S; Dabi, Y; Challine, A; Haddad, B; Herta, N; Souied, E; Ortala, M; Epaud, S; Masson, M; Salaün-Penquer, N; et al.
Abstract: Background: The COVID-19 pandemic has had a major impact on healthcare in many countries. This study assessed the effect of a nationwide lockdown in France on admissions for acute surgical conditions and the subsequent impact on postoperative mortality. Methods: This was an observational analytical study, evaluating data from a national discharge database that collected all discharge reports from any hospital in France. All adult patients admitted through the emergency department and requiring a surgical treatment between 17 March and 11 May 2020, and the equivalent period in 2019 were included. The primary outcome was the change in number of hospital admissions for acute surgical conditions. Mortality was assessed in the matched population, and stratified by region. Results: During the lockdown period, 57 589 consecutive patients were admitted for acute surgical conditions, representing a decrease of 20.9 per cent compared with the 2019 cohort. Significant differences between regions were observed: the decrease was 15.6, 17.2, and 26.8 per cent for low-, intermediate- and high-prevalence regions respectively. The mortality rate was 1.92 per cent during the lockdown period and 1.81 per cent in 2019. In high-prevalence zones, mortality was significantly increased (odds ratio 1.22, 95 per cent c.i. 1.06 to 1.40). Conclusion: A marked decrease in hospital admissions for surgical emergencies was observed during the lockdown period, with increased mortality in regions with a higher prevalence of COVID-19 infection. Health authorities should use these findings to preserve quality of care and deliver appropriate messages to the population. Abstract : This study assessed the change in acute surgical conditions during the lockdown period on a nationwide scale. There was an overall reduction in emergency operations of 20.9 per cent, with great variability according to prevalence of COVID-19 admissions. Mortality increased in regions with a high prevalence of COVID-19 infection.